2018
DOI: 10.1007/s00127-018-1500-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender differential in social and economic predictors of incident major depressive disorder in the Ibadan Study of Ageing

Abstract: PurposeWorking on the hypothesis that the social and economic factors associated with onset of late-life depression operate differently for men and women, we investigated the impact of current social relationships and lifetime occupational attainment on incident major depressive disorder (MDD) assessed in three follow-up waves over a period of 5 years.MethodsParticipants were part of a household multistage probability sample of 2149 Nigerians who were aged 65 years and above. The presence of current and lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…16 Such relationship is yet to be examined in LMICs. Third, in a series of studies by our group, 17,18 we found some of the highest global prevalence and incidence rates of late-life depression among Nigerian older persons. The extent to which the high rates of late-life depression impacts on onset, chronicity, or recovery from loneliness in people living in SSA is unknown.…”
Section: Introductionmentioning
confidence: 79%
“…16 Such relationship is yet to be examined in LMICs. Third, in a series of studies by our group, 17,18 we found some of the highest global prevalence and incidence rates of late-life depression among Nigerian older persons. The extent to which the high rates of late-life depression impacts on onset, chronicity, or recovery from loneliness in people living in SSA is unknown.…”
Section: Introductionmentioning
confidence: 79%
“…The mean number of lifetime episodes was approximately two. When assessed in three follow-up waves over a period of 5 years (Ojagbemi et al, 2018b), the incidence rate of MDD of 120.9 per 1000 person years (95% CI 110.4-132.5) was found among 1394 persons who were free of lifetime MDD and dementia at baseline. Incidence rates were 94.7 (95% CI 82.5-108.7) and 153.8 (95% CI 136.3-173.6) per 1000 person years in men and women, respectively (Ojagbemi et al, 2018b).…”
Section: The Ibadan Study Of Ageingmentioning
confidence: 99%
“…For example, prevalent MDD was associated with poor social engagement (Ojagbemi and Gureje, 2019 a ), loneliness (Ojagbemi and Gureje, 2019 a ) and increasing level of urbanisation in the place of residence (Gureje et al ., 2007) with odds ratios (OR) of 3.1, 2.3 and 1.4, respectively. Overall, poor social network was a key modifiable risk factor for incident MDD (Gureje et al ., 2011; Ojagbemi et al ., 2018 b ). Specifically, living in a rural location and having no regular contact with family (both of which can be regarded as indicators of poor social network) at baseline were associated with subsequent onset of MDD (Gureje et al ., 2011; Ojagbemi et al ., 2018 b ).…”
Section: Late-life Depression In the Isamentioning
confidence: 99%
See 2 more Smart Citations